Modeling economic growth in contemporary Poland - Bukalska, Elżbieta; Kijek, Tomasz; Sergi, Bruno S. (Entrepreneurship and global economic growth., 2023)
Over the past 15 years, Poland has been one of the fastest-growing countries in the European Union. Trying to explain the sources of Poland's economic success and decouple it from simple stylized facts on economic convergence anchored in the neoclassical growth models, the authors show how the Polish economy rapidly moved away from the communist economic system, which had ended up in an economic collapse, and moved towards unprecedented growth in income and the quality of life. Analyzing the transition and contemporary challenges of the Polish economy - including resilience to COVID and the Ukraine war, issues relating to Polish economic growth's institutional and policy framework, and the prospects of economic growth in Poland from the micro, mezzo, and macro perspectives - Modeling Economic Growth in Contemporary Poland is suitable for practitioners and academics interested in discovering the foundations for Polish growth, exploring whether this growth will likely last in the future. Entrepreneurship and Global Economic Growth presents modern examinations of economic growth at national, regional, and global levels. Each book in this series discusses different dimensions of the changing economic and industrial contexts and examines in detail their impact on the nature of growth and development.